Socialization and Digital Marketing Assistance to Micro, Small and Medium Enterprises (MSMEs) Squid Goyang By Applying Tamansiswa Teachings "TRI N (Niteni, Nirokke, Nambahi)" - Berlian, Aleandra Rizki; Ananda, Deanissa Setya; Rayona, Nyoman Rayya; Asy, Martinus Andika; Saputro, Enzo Sungsang; Utami, Sabina Sandriani; Kusuma, Nala Tri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Students of the Management Study Programme, Faculty of Economics, Sarjanawiyata Tamansiswa University (UST) held a community service activity with Micro, Small and Medium Enterprises (MSMEs) partner ‘Cumi Bergoyang’ located in the Alun-alun Kidul area of Yogyakarta. This activity aims to apply digital marketing to Cumi Bergoyang MSMEs in accordance with being able to compete with other businesses and reach a wider market share, this counseling and mentoring activity also applies the Tamansiswa Teachings, namely Tri N (Niteni, Nirokke, Nambahi) in helping MSMEs understand and implement digital marketing concepts. The method used in this abdimas activity is Participatory Learning and Action (PLA), which is given in accordance with the conditions of the partners and the needs of the problems faced by the abdimas partners, then the abdimas team provides solutions in the form of training programmes that involve hands-on practice using social media platforms Instagram and Tiktok as a means of promotion used in business activities. The implication of this abdimas activity is that MSME partners ‘Cumi Bergoyang’ can increase revenue turnover and maximise promotional reach in an increasingly competitive digital era.